2021
DOI: 10.1038/s41598-021-95931-6
|View full text |Cite
|
Sign up to set email alerts
|

A new nanomagnetic Pd-Co bimetallic alloy as catalyst in the Mizoroki–Heck and Buchwald–Hartwig amination reactions in aqueous media

Abstract: A Pd-Co bimetallic alloy encapsulated in melamine-based dendrimer supported on magnetic nanoparticles denoted as γ-Fe2O3@MBD/Pd-Co was synthesized by a facile co-complexation-reduction method and characterized sufficiently. The catalytic evaluation of γ-Fe2O3@MBD/Pd-Co showed promising results in the Mizoroki–Heck and Buchwald–Hartwig amination reactions of various iodo-, bromo- and challenging chloroarenes in aqueous media. The synergetic cooperative effect of both Pd and Co and dispersion of the catalyst in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Then, the reaction proceeds by the coordination of aniline with intermediate (I) to form intermediate (II). Finally, the product is formed by base-assisted elimination of X-H from intermediate (III) by subsequent reductive elimination and catalyst regeneration . In the oxidation process, TBHP cleaves to yield the peroxo compound and tert-butanol ( t -BuOH) resulting in the peroxo surface species.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the reaction proceeds by the coordination of aniline with intermediate (I) to form intermediate (II). Finally, the product is formed by base-assisted elimination of X-H from intermediate (III) by subsequent reductive elimination and catalyst regeneration . In the oxidation process, TBHP cleaves to yield the peroxo compound and tert-butanol ( t -BuOH) resulting in the peroxo surface species.…”
Section: Resultsmentioning
confidence: 99%
“…The substrate scope was further expanded to piperidine (11)(12)(13)(14)(15)(16)(17) and their derivatives, i.e. morpholine (18)(19)(20) and piperazine (21-23) (Fig.…”
Section: Substrate Scopementioning
confidence: 99%
“…In the past decades, there were several reports of bimetallic strategies which utilise Ni-Cu, Pd-Au, Pd-Fe, Pd-Co and Pd-Cu, all of which strongly demand the presence of base for the desired transformation. [8][9][10][11][12] The presence of strong bases in C-N coupling reactions gives rise to interference with base sensitive and electron withdrawing groups, and also induces precipitation, restricting the use of such methodologies in bulk batch reactions and in flow or micro-channel reactors. Recently Patil et al, (2019), followed by Joshi et al, (2020), reported a base free methodology for C-N coupling reactions which addressed the raised issues to certain extents.…”
Section: Introductionmentioning
confidence: 99%
“…In continue of our studies on the introducing new heterogeneous catalysts for the organic transformations 35 37 , herein, in this paper, we have applied a MOF modified with cobalt-complex 38 [Co-isatin-Schiff-base-MIL-101(Fe)] as a new heterogeneous multifunctional bio-photocatalyst for the synthesis of benz-imidazoles/-oxazoles/-thiazoles, and benzylidene malononitrile by TOP starting from readily available alcohols. The photocatalytic antibacterial activity of Co-isatin-Schiff-base-MIL-101(Fe) against E. coli, S. aureus and S. pyogenes was also studied under sunlight illumination.…”
Section: Introductionmentioning
confidence: 99%